2013
DOI: 10.1093/mnras/stt1573
|View full text |Cite
|
Sign up to set email alerts
|

Optical observations of PSR J0205+6449 – the next optical pulsar?

Abstract: PSR J0205+6449 is a young (∼ 5400 years), Crab-like pulsar detected in radio and at X and γ-ray energies and has the third largest spin-down flux among known rotationpowered pulsars. It also powers a bright synchrotron nebula detected in the optical and X-rays. At a distance of ∼ 3.2 kpc and with an extinction comparable to the Crab, PSR J0205+6449 is an obvious target for optical observations. We observed PSR J0205+6449 with several optical facilities, including 8m class ground-based telescopes, such as the G… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
17
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
1
1

Relationship

5
3

Authors

Journals

citations
Cited by 8 publications
(22 citation statements)
references
References 55 publications
(111 reference statements)
5
17
0
Order By: Relevance
“…This yields F opt /F X ∼ 3.1 × 10 −4 and F opt /F γ ∼ 3.5 × 10 −6 . All of these values are in the range of those computed for the other middle aged pulsars identified in the optical (see, e.g., Table 4 of Moran et al 2013). This confirms that middle aged pulsars tend to have similar multi-wavelength emission properties.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…This yields F opt /F X ∼ 3.1 × 10 −4 and F opt /F γ ∼ 3.5 × 10 −6 . All of these values are in the range of those computed for the other middle aged pulsars identified in the optical (see, e.g., Table 4 of Moran et al 2013). This confirms that middle aged pulsars tend to have similar multi-wavelength emission properties.…”
Section: Discussionsupporting
confidence: 83%
“…Furthermore, candidate counterparts have been found for PSR J0205+6449 (Moran et al 2013) and PSR J1357−6429 (Zyuzin et al 2016). Here, we found a candidate counterpart to another γ-ray pulsar, PSR J1741−2054.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…Owing to their intrinsic faintness, the number of pulsar detections at optical energies by and large lag behind those at high energies. After the Crab pulsar (PSR B0531+21; Cocke et al 1969), which was the first one identified through its optical pulsations at the radio period (Cocke et al 1969), only eight isolated pulsars (i.e., not in binary systems) have been firmly identified in the optical plus two candidates (see, Mignani 1 See, ATNF pulsar catalogue (Manchester et al 2005) 2011 for a review), and three more identifications have been recently proposed (Moran et al 2013;Mignani et al 2016a;Rangelov et al 2017). Optical pulsations have been detected only for some of them, though.…”
Section: Introductionmentioning
confidence: 99%
“…Owing to their faintness, only eight of the over 200 γ-ray pulsars discovered to date 6 have been detected at optical wavelengths (see Abdo et al 2013 and references therein), the number accounting also for PSR B0540−69 (Caraveo et al 1992), only recently found to be a γ-ray pulsar (Ackermann et al 2015). Furthermore, candidate counterparts have been found for PSR J0205+6449 (Moran et al 2013) and PSR J1357−6429 (Zyuzin et al 2016). Here, we found a candidate counterpart to another γray pulsar, PSR J1741−2054.…”
Section: Discussionmentioning
confidence: 99%